2017
DOI: 10.1039/c6ra26331c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the photophysical properties of BODIPY dyes through extended aromatic pyrroles

Abstract: A series of naphthyl and fluorantho-fused BODIPY dyes have been synthesized by a simple two-step process. These dyes display high molar absorptivities in the far visible region of the spectrum with emission quantum efficiencies at or near unity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“… [18] Even more interesting is the possibility to tune the emission of these species, by introducing small modifications[ 19 , 20 ] and/or extending the conjugation around the fluorescent core. [21] BODIPY type species are extremely versatile as well, thanks to their high photo [22] and chemical stability [23] and their high solubility even in aqueous media. [24] Other classes of ligands, either N,N [25] or N,O [26] chelating, proved to be useful in the synthesis of highly emissive boron compounds as well.…”
Section: Introductionmentioning
confidence: 99%
“… [18] Even more interesting is the possibility to tune the emission of these species, by introducing small modifications[ 19 , 20 ] and/or extending the conjugation around the fluorescent core. [21] BODIPY type species are extremely versatile as well, thanks to their high photo [22] and chemical stability [23] and their high solubility even in aqueous media. [24] Other classes of ligands, either N,N [25] or N,O [26] chelating, proved to be useful in the synthesis of highly emissive boron compounds as well.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing π-electron conjugation of similar emissive organic chromophores normally results in enhanced fluorescent emission, as well as red shifts in excitation and emission wavelengths. This strategy is applied in system 4 , a naphthyridin derivative in which the π-conjugation is extended by fusing the pyrrole units with other aromatic rings. We found that the absorption maximum is red-shifted in +54 nm (−0.303 eV) and emission in +95 nm (−0.419 eV), with respect to 2 , as a result of the donor effect of the added rings (see EDD map).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing π-electron conjugation of similar emissive organic chromophores normally results in enhanced fluorescent emission, as well as redshifts in excitation and emission wavelengths [61][62][63][64] . This strategy is applied in system 4, a naphthyridin derivative 65 where the πconjugation is extended by fusing the pyrrole units with other aromatic rings.…”
Section: Structure-property Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it does pose an interesting exercise to evaluate the effect of combining two complexes with rich electrochemical and spectroscopic properties in such a way that favors electronic communication. To that end this laboratory has adapted our previously reported solid state dipyrrin reactions utilizing π-extended pyrroles , to incorporate within the pyrrole unit nitrogen coordination sites. In this report, we describe the synthesis and characterization of new Bodipy dyes formed from isoquinopyrrole and a variety of aldehydes.…”
Section: Introductionmentioning
confidence: 99%